1997
DOI: 10.1016/s0009-2509(97)00248-0
|View full text |Cite
|
Sign up to set email alerts
|

Absorption accompanied with chemical reaction in trickle-bed reactors

Abstract: Pergamon ('hcm~,ai f~mt.wcrl.a .gclenc(.. Vo] Abstraet---A new development in the field of internals in packed columns is the use of structured packing types. Recently, a new structured packing type coated with a thin alumina layer (KATAPAK rM) has been developed, in this report, the results of an experimental and theoretical study concerning the possible applicability of this new packing material for hydrogenation processes in a trickle-bed reactor is presented. The palladium catalyzed hydrogenation of ~-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Another work of structured packing in cocurrent downward mode was reported by Nijhuis et al (2001) with monolithic catalyst. In contrast to the results of Versteeg et al (1997), they have reported better performance in terms of productivity of the monolithic catalyst for the hydrogenation of α-methylstyrene and better selectivity for the hydrogenation of benzaldehyde to benzylalchol. Though this type of reactor may be advantageous for some specific reactions, it cannot be useful, in general, considering the point of catalyst utilization per reactor volume and mass transfer driving force.…”
Section: Structured Catalytic Packing With Cocurrent Downward Flowcontrasting
confidence: 72%
“…Another work of structured packing in cocurrent downward mode was reported by Nijhuis et al (2001) with monolithic catalyst. In contrast to the results of Versteeg et al (1997), they have reported better performance in terms of productivity of the monolithic catalyst for the hydrogenation of α-methylstyrene and better selectivity for the hydrogenation of benzaldehyde to benzylalchol. Though this type of reactor may be advantageous for some specific reactions, it cannot be useful, in general, considering the point of catalyst utilization per reactor volume and mass transfer driving force.…”
Section: Structured Catalytic Packing With Cocurrent Downward Flowcontrasting
confidence: 72%
“…Studies on gas-and liquid-side mass transfer and separation efficiency [10,11,14,16,20,21,24,25] were carried out to provide design correlations and performance characteristics. Some recent papers deal with gas-liquid mass transfer in trickle-flow conditions [14,25]. Together with other research work [20±22] they give information on the behavior of a new catalytically active structured packing developed by Sulzer, the inventor of the first corrugated sheet packing.…”
Section: Introductionmentioning
confidence: 99%